O-077 The chromosomal constitution of embryos developing from 0PN zygotes. (30th June 2022) - Gomez Peña, M; Papayannis, M; De Martino, E; Filardi, P; Magri, L; Chiarello, J M; Figueroa, C; De Zuñiga, I; Kopcow, L; Horton, M; Sobral, F; Oubiña, A; et al.
Abstract: Study question: To compare the ploidy status of embryos originated from zygotes with absence of pronuclei (0PN) with those developing from normal two pronuclei (2PN) fertilization. Summary answer: We did not find significant differences in euploidy rates between blastocysts from 0PN and 2PN zygotes. What is known already: Information regarding the ploidy number of 0PN zygotes, even when the pronuclei number is assessed by time-lapse microscope coupled incubators, is still insufficient. Because of this, embryos originating from 0PN zygotes are usually discarded or individualized in order not to include them in first transfers. Even more, abnormal fertilization is considered as a proxy of poor embryo quality. Study design, size, duration: A retrospective observational study from March 2016 and December 2021 including 80 PGT-A cycles in which at least one of the blastocysts studied developed from oocytes in which pronuclei were not seen at the time of fertilization check. Participants/materials, setting, methods: 307 blastocysts were studied, of which 115 originated from 0PN and 192 from 2PN zygotes. Pronuclear number was assessed 16-20 h after insemination. Zygotes with 0PN were cultured separately from 2PN ones of the same cohort. After extended culture, a biopsy was performed and the material obtained was genetically studied using Next Generation Sequencing. Statistical comparisons were made with Fisher's exact and Chi-square tests. Significance level was set at P <0.05. Main results and the role of chance: No differences were observed in euploidy rates between the 2PN and 0PN groups [55.2% (106/193) VS 43.5% (50/115)]. In aneuploid embryos originating from 2PN zygotes, a similar amount of trisomies and monosomies was observed (56 and 56 respectively). In contrast, aneuploid embryos from 0PN oocytes showed a greater number of trisomies than monosomies (55 and 35 respectively, P < 0.05). None of the blastocysts resulting from 0PN was haploid, that is, we did not find parthenogenic embryos. Blastocysts derived from 0PN zygotes showed similar quality scoring than those from 2PN ones. To date, 20 euploid blastocysts from the 0PN group have been transferred, producing 12 pregnancies: 6 still ongoing and 4 healthy live births. Limitations, reasons for caution: Non-visualization of pronuclei in oocytes that later generate normal diploid blastocysts may be due to a faster or slower cell cycle progression. Modifications in the daily fertilization check schedules of busy laboratories should also be considered. Wider implications of the findings: Contrary to expectations, aneuploid embryos from 0PN oocytes showed a greater number of trisomies than monosomies. A significant fraction of the embryos generated from 0PN zygotes were actually diploid, with similar quality and outcome results than 2PN ones. This makes them perfectly usable in IVF routines. Trial registration number: Not applicable